2021
DOI: 10.1177/20597002211006551
|View full text |Cite
|
Sign up to set email alerts
|

A review of minor traumatic brain injury presentations and their management in Brisbane emergency departments

Abstract: Objective A retrospective audit of minor traumatic brain injury presentations to three Brisbane emergency departments aiming to assess rates of CT scans and compliance with the Canadian CT Head Rule (CCTHR), as well as reviewing the demographics of patients and their management. Method Minor traumatic brain injury presentations to the Emergency departments of the Royal Brisbane and Women’s Hospital, Redcliffe Hospital and Queen Elizabeth II Hospital between July 1st and August 30th, 2019 were identified via di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These ndings are in agreement with previous studies which also reported skull fractures as the most common abnormal CT scan nding in patients with mild head injury. This was found to be at 43% and 8.9% in studies done in Zagazig university, Egypt and in Brazil respectively (21,22). In our setting, skull fractures were the most common abnormal CT scan nding likely due to the mechanisms of injury involving motorcycle riders and assaults that are high risk factors for skull fractures.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…These ndings are in agreement with previous studies which also reported skull fractures as the most common abnormal CT scan nding in patients with mild head injury. This was found to be at 43% and 8.9% in studies done in Zagazig university, Egypt and in Brazil respectively (21,22). In our setting, skull fractures were the most common abnormal CT scan nding likely due to the mechanisms of injury involving motorcycle riders and assaults that are high risk factors for skull fractures.…”
Section: Discussionmentioning
confidence: 52%
“…However, two studies done in Brisbane Australia and Southern California showed comparable ndings to our study with the proportion of appropriate CT scans performed higher than the inappropriately performed CT scans. The proportions of appropriate CT scans based on the CCHR were found to be 91% and 63.2% for the study in Brisbane and Southern California respectively (22,23). For the study in Brisbane, CCHR had already been introduced for use in their ED and the study was assessing the compliance, this might explain the high proportion obtained.…”
Section: Discussionmentioning
confidence: 95%